2020
DOI: 10.15740/has/ijas/16.2/244-248
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of chickpea varieties under frontline demonstration at farmer’s field in Bhind district of M.P.

Abstract: The study was carried out to know the gap between improved packages of practices in gram crop. Frontline demonstration on gram varieties J.G.16, JAKI 92-18 and J.G. 130 were conducted at farmer's field in the adopted village of Krishi Vigyan Kendra, Lahar Bhind (M.P.) during the years 2010-11 to 2014-15. The average yield of J.G. 16 variety was 18.07 q/ha. J.G. 16 has given 20.4 q/ha. Highest yield during the year under frontline demonstration while local varieties gave 16.61 q/ha average yield during the year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…The results of this article allow us to develop more effective road safety plans taking into account these seasonal events. In [6][7], the application of the ARIMA model for predicting deaths in RTAs in India is investigated and the growth of RTAs is predicted, which emphasizes the relevance of these studies. In the article [8], the authors considered the time series of RTAs in Serbia (Belgrade) using the SARIMA model and as a result found that the time series has a pronounced seasonal character.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this article allow us to develop more effective road safety plans taking into account these seasonal events. In [6][7], the application of the ARIMA model for predicting deaths in RTAs in India is investigated and the growth of RTAs is predicted, which emphasizes the relevance of these studies. In the article [8], the authors considered the time series of RTAs in Serbia (Belgrade) using the SARIMA model and as a result found that the time series has a pronounced seasonal character.…”
Section: Introductionmentioning
confidence: 99%